Tax Avoidance: Peran Komisaris Independen, Kepemilikan Institusional dan Intensitas Modal - Almaida Quata; Amir Hidayatulloh (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to analyze the influence of independent commissioners, institutional ownership, and capital intensity on tax avoidance practices in companies listed on the Kompas 100 index in 2024. This study uses a quantitative approach with secondary data from financial statements and annual reports. The sample was determined through purposive sampling and obtained 67 companies. The analysis was conducted using multiple linear regression with SPSS. This study found that tax avoidance was not affected by independent commissioners, institutional ownership, and capital intensity